5-ALA and FDA Approval for Glioma Surgery - Hadjipanayis, Constantinos G. (J Neurooncol, 2019)
The U.S. Food and Drug Administration (FDA) approved 5-ALA (Gleolan®; photonamic GmbH & Co. KG) for use as an intraoperative optical imaging agent in patients with suspected high-grade gliomas (HGGs) in 2017. This was the first ever optical imaging agent approved as an adjunct for the visualization of malignant tissue during surgery for brain tumors. The approval occurred a decade after European approval and a multicenter, phase III randomized trial which confirmed that surgeons using 5-ALA FGS as a surgical adjunct could achieve more complete resections of tumors in HGG patients and better patient outcomes than with conventional microsurgery. Much of the delay in the US FDA approval of 5-ALA stemmed from its conceptualization as a therapeutic and not as an intraoperative imaging tool. We chronicle the challenges encountered during the US FDA approval process to highlight a new standard for approval of intraoperative optical imaging agents in brain tumors.